AQUEOUS EXTRACTS OF Xylopia aromatica AND Annona crassiflora ON MARANDU GRASS (Brachiaria brizantha) AND SOYBEAN - INOUE, Miriam Hiroko; SANTANA, Diogo Carneiro de; PEREIRA, Mônica Josene Barbosa; POSSAMAI, Ana Cássia Silva; AZEVEDO, Virgínia Helena de (Scientia Agraria, 2009)
The inhibitory effect of Xylopia aromatica and Annona crassiflora (Annonaceae) aqueous extracts on marandu grass (Brachiaria brizantha) and soybean (Glycine max) was evaluated. For such purpose germination tests (25 ºC and photoperiod of 12 h) and radicle and hypocotyl development (25 ºC and photoperiod of 24 h), were measured during 10 days. Extracts were obtained through plant infusion in distilled water for 24 h. Treatments were arranged in 3 x 6 factorial scheme in randomized block design using four replications. Extracts of seeds, leaves, and branches of X. aromatica or A. crassiflora were used in the concentrations of 20, 40, 60, 80 and 100 g dm-3, besides an absolute check in distilled water. With exceptions of the extracts with 20 g dm-3 (branches of X. aromatica and A. crassiflora) and 40 g dm-3 (leaves of X. aromatica), all treatments with aqueous extracts inhibited germination of B. brizantha, showing the allelopathic activity of X. aromatica and A. crassiflora. It was verified that extracts of A. crassiflora interfered on the radicle development of B. brizantha. However, only seeds extracts of A. crassiflora interfered in the soybean germination.